Achieving universal testing for malaria. (4th February 2016) - Ochodo, Eleanor; Garner, Paul; Sinclair, David
Abstract : Rapid diagnostic tests have the potential to reduce the overtreatment of malaria by 95%, but time and extensive logistical, behavioural, and technical interventions may be required to achieve this, argue Eleanor Ochodo and colleagues